2016
DOI: 10.1159/000446645
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Biomaterials to Influence Oligodendroglial Growth, Maturation, and Myelin Production

Abstract: Millions of people suffer from damage or disease to the nervous system that results in a loss of myelin, such as through a spinal cord injury or multiple sclerosis. Diminished myelin levels lead to further cell death in which unmyelinated neurons die. In the central nervous system, a loss of myelin is especially detrimental because of its poor ability to regenerate. Cell therapies such as stem or precursor cell injection have been investigated as stem cells are able to grow and differentiate into the damaged c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 103 publications
0
16
0
Order By: Relevance
“…Compared to long-chain-length PEG, hydrogels derived from shorter-chain-length PEGs possessed a higher cross-linking density that resulted in a stiffer material and led to higher expressions of PDGFRα. 52 These studies reinforce the importance of modulating mechanical properties to fit the differentiating neural 53 , 54 or glial cells 55 , 56 for treating SCI.…”
Section: Introductionmentioning
confidence: 55%
“…Compared to long-chain-length PEG, hydrogels derived from shorter-chain-length PEGs possessed a higher cross-linking density that resulted in a stiffer material and led to higher expressions of PDGFRα. 52 These studies reinforce the importance of modulating mechanical properties to fit the differentiating neural 53 , 54 or glial cells 55 , 56 for treating SCI.…”
Section: Introductionmentioning
confidence: 55%
“…OPCs clearly merit consideration as a therapeutic option targeting remyelination in MS, with the delivery of exogenous OPCs to demyelinated areas; however, there remain several outstanding issues (66). Many of these are addressed in an extensive review published recently by Unal et al (67).…”
Section: Issues Related To the Administration Of Opcs Through Particlmentioning
confidence: 99%
“…18 Hydrogel cell culture models enable interrogation of the roles that extracellular cues such as matrix stiffness play in regulating salient cell behaviors. 10,[19][20][21] Jagielska et al showed that OPCs are mechanosensitive, with proliferation being greatest on 2D substrates with Young's elastic moduli of 700 Pa. 22 3D culture systems offer the potential to study cell-cell and cell-matrix interactions as well as biotransport conditions in a more physiologically-relevant setting. We previously showed that OPC metabolic activity was greatest within 3D PEG hydrogels with storage moduli of 240 ± 84 Pa in comparison to 630 ± 79 Pa. 23 In this work, we used 3D HA hydrogels to interrogate the effects of stiffness and mesh size on OPC proliferation, metabolic activity, and spheroid volume.…”
Section: Introductionmentioning
confidence: 99%